Strategi Guru PAI dalam Meningkatkan Minat Belajar (Motivasi) Pembelajaran PAI di SMAN 1 Colomadu Karanganyar - Mahmud Darul Kurniyadi; Meti Fatimah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Learning activities can achieve success if they use the right learning strategy. However, the reality in the field is that there are still Islamic religious education teachers who have not used strategies in the classroom learning process. This is due to a lack of knowledge about effective teaching methods. This results in the teaching approach used is not in accordance with the needs of today's students. This study aims to identify and analyze the strategies applied by Islamic Religious Education (PAI) teachers in increasing students' interest and learning outcomes (motivation) at State Senior High School 1 Colomadu, Karanganyar. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation conducted on PAI teachers, students, and other related parties. The results showed that PAI teachers at SMA Negeri 1 Colomadu used various strategies, such as the implementation of interactive learning, the use of relevant learning media, and a personal approach to students to increase learning motivation. In addition, giving awards and emphasizing the relevance of the material to daily life also play an important role in increasing students' interest in learning. These strategies have proven effective in generating learning motivation and improving student learning outcomes, although there are still challenges that need to be overcome, such as limited time and facilities. This research is expected to provide insights for the development of PAI learning in other schools.